2010
DOI: 10.1177/1479972310368691
|View full text |Cite
|
Sign up to set email alerts
|

COPD, chronic bronchitis and capacity for day-to-day activities: Negative impact of illness on the health-related quality of life

Abstract: The aim of this study was to investigate the negative impact of illness on health-related quality of life (HRQoL) of people with chronic obstructive pulmonary disease (COPD) or chronic bronchitis. The study population consisted of the participants (N ¼ 8028) of a health examination survey conducted in Finland. The sample in the present substudy was composed of 4718 participants who had complete information about spirometry. Variables age, gender, body mass index (BMI), illnesses, smoking in lifetime, education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…Several studies have reported worse health outcomes for subjects with CB and normal lung function than for healthy subjects, including a greater risk of COPD, hospitalization and death [7,29]. Subjects with CB may also have poorer physical fitness, and they may be limited in their daily activities and exercise [30]. Self-limitation of physical activity and a sedentary lifestyle could at least in part explain our findings also in this group.…”
Section: Discussionsupporting
confidence: 50%
“…Several studies have reported worse health outcomes for subjects with CB and normal lung function than for healthy subjects, including a greater risk of COPD, hospitalization and death [7,29]. Subjects with CB may also have poorer physical fitness, and they may be limited in their daily activities and exercise [30]. Self-limitation of physical activity and a sedentary lifestyle could at least in part explain our findings also in this group.…”
Section: Discussionsupporting
confidence: 50%
“…Females tend to have a greater sensitivity to their perception of physical stimuli, particularly unpleasant experimental or chronic pain (Edwards, 2003). Women with chronic obstructive pulmonary disease have poorer health related quality of life than men (Kanervisto, 2010) and have a 2–3 fold higher suicide risk (Webb, 2012). Women with respiratory disorders, such as COPD, self-report more psychological distress than men (Laurin 2007; Di Marco et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show significant emotional and physical adaptation that has also been reported in previous studies on COPD. [15][16][17][18][19][20][21][22][23] Participants remarkably emphasize what they can achieve, despite multimorbidity, leading to a generally positive perception of functional status. Although we confirm that fear is a central point of attention in patients with COPD, this does not seem to be merely related to dyspnea and fear of suffocating.…”
Section: Discussionmentioning
confidence: 99%